Effect of lignocellulosic biomass inhibitors on oleaginous yeast cultivation in multistage fermentation system. (September 2021) - Sharma, Tripti; Sailwal, Megha; Dasgupta, Diptarka; Hazra, Saugata; Bhaskar, Thallada; Ghosh, Debashish
Abstract: In this study, the natural resistance of oleaginous yeast Rhodotorula mucilagenosa (RMIIPL32) is assessed against lignocellulosic biomass derived five major inhibitors. Acetic acid (AA) had slight effect on the cell growth whereas, lipid yield increased to 8.9 g/g fatty acid methyl ester (FAME) content with comparison to control i.e., 7.2 g/g. Furfural (FF) at 1.5 g/L inhibited 50% biomass yield and lipid content was 4.29 g/g. 5- Hydroxymethylfurfural (HMF), vanillin (V) and syringaldehyde (S) at 2 g/L had slight inhibitory effect on lipid production but, negligible effect on the cell growth. These results demonstrate that the synergistic effect of inhibitors was toxic for the cell growth due to FF (1.5 g/L) and AA (2 g/L). RMIIPL32 can be considered for biomass derived C5 fermentation, as it accumulated lipids effectively in the presence significant concentrations of the inhibitors' without any change in lipid composition. Graphical abstract: Unlabelled Image Highlights: Reported oily yeast possess natural resistance to lignocellulosic inhibitors Acetic acid > Furfural >5-HMF, found to be inhibitory for oleaginous yeast The inhibitors had no effect on the lipid composition.